1982
DOI: 10.1042/bj2010241
|View full text |Cite
|
Sign up to set email alerts
|

Evidence from electron-paramagnetic-resonance spectroscopy for a complex of sulphite ions with the molybdenum centre of sulphite oxidase

Abstract: Reduction of sulphite oxidase by sulphite at low pH values in Mes (4-morpholine-ethanesulphonic acid) buffer gives rise to a new molybdenum(V) electron-paramagnetic-resonance spectrum different from that obtained by photoreduction of the enzyme in the same medium. The spectrum is attributed to a sulphite complex of the enzyme, showing g-values of about 2.000, 1.972 and 1.963. The complex is analogous to that with the inhibitor phosphate in that it gives rise to no observable hyperfine coupling of Mo(V) to exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 6 publications
5
43
0
Order By: Relevance
“…The signal generated under the experimental conditions used (reduction by sulfite followed with partial reoxidation by ferricyanide) also lacks the strongly coupled proton typically seen 316 (which had also been seen previously under at least certain conditions with the chicken enzyme 317 ), and the signal-giving species has been interpreted as a LMo V O(O–SO 3 − )(S–Cys) center with product sulfate coordinated to the molybdenum in place of the equatorial Mo=O. The g-values for this signal, in which product is blocked from dissociation, are g 1,2,3 = 2.005, 1.974, 1.963, very similar to the parameters for the ordinary low-pH spectrum (generated by partial reduction of enzyme with Ti III ·citrate), g 1,2,3 = 2.006, 1.975, 1.968.…”
Section: The Sulfite Oxidase Familysupporting
confidence: 68%
“…The signal generated under the experimental conditions used (reduction by sulfite followed with partial reoxidation by ferricyanide) also lacks the strongly coupled proton typically seen 316 (which had also been seen previously under at least certain conditions with the chicken enzyme 317 ), and the signal-giving species has been interpreted as a LMo V O(O–SO 3 − )(S–Cys) center with product sulfate coordinated to the molybdenum in place of the equatorial Mo=O. The g-values for this signal, in which product is blocked from dissociation, are g 1,2,3 = 2.005, 1.974, 1.963, very similar to the parameters for the ordinary low-pH spectrum (generated by partial reduction of enzyme with Ti III ·citrate), g 1,2,3 = 2.006, 1.975, 1.968.…”
Section: The Sulfite Oxidase Familysupporting
confidence: 68%
“…Distinct EPR forms with coordinated phosphate (11, 26) and arsenate (9) have also been observed at low pH. It has also been suggested that the blocked form actually contains bound sulfite, the reactant, which is present in large excess in the EPR samples (27, 28). …”
Section: Resultsmentioning
confidence: 99%
“…Electron transfer from Mo IV to Fe III heme can in principle precede or follow SO 4 2− dissociation [13]. Indeed, so-called blocked forms of the enzyme are suggested to possess a SO 4 2− product bound to Mo V [13] although a SO 3 2− substrate bound to Mo V was also detected under high SO 3 2− concentrations by EPR spectroscopy [35][36][37]. Hence, both product and substrate can block the active site.…”
Section: The Mononuclear Molybdenum Enzymesmentioning
confidence: 98%
“…The phosphane dissociation allows for coordination of hydroxide at the resulting free coordination site giving the above mentioned hydroxido oxido complex Mo V (L) 2 O(OH) and hence closing the catalytic cycle [93,96]. Interestingly, in a mutant of human sulfite oxidase strong EPR evidence suggests that the substrate sulfite can indeed coordinate to the molybdenum(V) center forming an off-loop species [35][36][37]. Similarly, the substrate xanthine can bind to Mo V in XO yielding an off-loop species [39].…”
Section: (S = ½) In the Oxido-bridged Molybdenum(v) Complexes [Mo(l)mentioning
confidence: 99%